Effective synthesis of bicyclodienes via palladium-catalyzed asymmetric allylic alkylation and ruthenium-catalyzed cycloisomerization - HAVARE, Nizam (Turk J Chem, 2020)
[n.3.0]Bicycles (n = 3–6) can be synthesized using palladium-catalyzed asymmetric allylic alkylation followed by ruthenium-catalyzed cycloisomerization. New types of triarylphosphino-1,2-diaminooxazoline ligands show the same high levels of enantioselectivity observed with Trost ligand when employed in Pd-catalyzed allylic alkylation reactions. The enyne products of these allylic alkylation reactions were further elaborated using a Ru-catalyzed redox isomerization process, for which a mechanism is proposed.